Povidone‐iodine lowers the incidence of catheter‐associated bloodstream infection. Issue 3 (18th March 2019) - Sugiyama, Minako; Iguchi, Akihiro; Terashita, Yukayo; Ohshima, Junjiro; Cho, Yuko
Abstract: Background: Central venous (CV) catheters are required for chemotherapy but they may become a source of life‐threatening infections of the bloodstream. The most effective way to disinfect the port of a CV catheter has not been established. Methods: We report the data obtained between April 2008 and March 2010 using 83% ethanol (period I) and between April 2010 and March 2014 using 10% povidone‐iodine (period II) to sterilize the access port. The participants received chemotherapy or autologous/allogeneic stem cell transplantation at the present institution. Results: No significant difference was observed in patient characteristics between the two periods, such as disease, median age, or the period of neutropenia. The incidence of positive blood culture during periods I and II was 18.5% (31/168) and 11.4% (40/350; P = 0.041), respectively. The incidence of catheter‐associated bloodstream infection on blood culture during periods I and II was 11.9% (20/168) and 6.3% (22/350; P = 0.043), respectively. Bacillus cereus infection was not detected during period II. Conclusion: The incidence of infection caused by CV catheters was significantly reduced using povidone‐iodine; therefore, we recommend this procedure as part of the routine in chemotherapy.